Lack Of Sharia Financial Literacy as A Factor Causing Less Attention to Sharia Factoring In Indonesia - Rini Fitriani; Nahdiya Asna; Nana Alfiana (JOURNAL OF SHARIA ECONOMICS, 2023)
Many Islamic financial institutions offer various Sharia-compliant financial products, including Islamic factoring. Islamic factoring is regulated by the National Sharia Board Fatwa (DSN) Number 67/DSN-MUI/III/2008. Islamic factoring is the process of transferring short-term receivables of a company in accordance with Sharia principles. It is one of the financing options for companies that use installment or deferred payments to boost sales. However, implementing sales with installment or deferred payments can pose problems if not done through a legal third party. This third party can be an Islamic factoring company or an Islamic financial institution that offers Islamic factoring products. Despite the presence of many companies in Indonesia, both listed on the Indonesia Stock Exchange and unlisted, whether state-owned or private, the growth of Islamic factoring in Indonesia has not kept pace with overall growth. Therefore, this research aims to explore the factors that contribute to the lack of interest in Islamic factoring in Indonesia. The research method employed is a literature study using written data from journal articles, books, and reliable documents such as the Financial Services Authority website. Data analysis is conducted using a descriptive approach. The research findings indicate that one of the factors causing the lack of interest in Islamic factoring is the low level of financial literacy in Sharia among the public.